ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): JOB ROLE CHARACTERISTIC AND ORGANIZATIONAL CULTURE WITH IMPROVING EMPLOYEE JOB SATISFACTION - Yanto, Wahyu Budi; Suhud, Usep Suhud; Purwohedi, Unggul Purwohedi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
The aims of study were to examine and analyze the effect of job characteristics and culture on satisfaction and OCB in Jakarta Customs and Excise Office Employees. The research was conducted by the Jakarta Customs and Excise Office. The research population were 1,403 employees at the Jakarta Customs and Excise Office. The number of samples were 294 employees. The data analysis method used validity, reliability, normality tests, linearity tests, classical assumption tests and path analysis. The results showed that job characteristics did not significantly affect the OCB of the Jakarta Customs and Excise Office employees. Organizational culture had a positive effect on OCB of Jakarta Customs and Excise Office employees. Job characteristics have no significant effect on job satisfaction of Jakarta Customs and Excise Office employees. Organizational culture has a positive effect on job satisfaction of Jakarta Customs and Excise Office employees. Employee job satisfaction had a positive effect on the formation of OCB behavior of the Jakarta Customs and Excise Office employees.Â